Adhesives with different pHs: Effect on the MTBS of chemically activated and light-activated composites to human dentin - Mallmann, Andre; de Melo, Renata Marques [UNESP]; Estrela, Verbenia; Pelogia, Fernanda [UNESP]; Campos, Laura; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2007)
Purpose: To evaluate the bond strength between human dentin and composites, using two light-activated single-bottle total-etch adhesive systems with different pHs combined with chemically activated and light-activated-composites. The tested hypothesis was that the dentin bond strength is not influenced by an adhesive system of low pH, combined with chemically activated or light-activated composites. Material and Method: Flat dentin surfaces of twenty-eight human third molars were allocated in 4 groups (n=7), depending on the adhesive system: (One Step Plus-OS and Prime & Bond NT-PB) and composite (light-activated Filtek Z-100 [Z100] and chemically activated Bisfil 2B [B2B]). Each adhesive system was applied on acid-etched dentin and then one of the composites was added to form a 5 mm-high resin block. The specimens were stored in tap water (37 degrees C/24 h) and sectioned into two axes, x and y. This was done with a diamond disk under coolant irrigation to obtain beams with a cross-section area of approximately 0.8 mm(2). Each specimen was then attached to a custom-made device and submitted to the microtensile test (1 mm.min(-1)). Data were analyzed using two-way ANOVA and Tukey's tests (p<0.05). Results: the anticipated hypothesis was not confirmed (p<0.0001). The bond strengths (MPa) were not statistically different between the two adhesive systems when light-activated composite was used (OS+Z100 = 24.7 +/- 7.1(a); PB+Z100 = 23.8 +/- 5.7(a)). However, with use of the chemically activated composite (B2B), PB (7.8 +/- 3.6(b) MPa) showed significantly lower dentin bond strengths than OS (32.2 +/- 7.6(a)). Conclusion: the low pH of the adhesive system can affect the bond of chemically activated composite to dentin. on the other hand, under the present conditions, the low pH did not seem to affect the bond of light-activated composites to dentin significantly.
Keywords: tensile-strength; dentin-bonding agents; composite resins